How to think like a scientist : answering questions by the scientific method - Kramer, Stephen P.; Bond, Felicia (New York : T.Y. Crowell, 1987)
Uses questions about hypothetical situations to introduce the process of thinking according to scientific method.
Includes index.
Keywords: Science -- Methodology -- Juvenile literature; Science -- Methodology